2017
DOI: 10.3390/ma11010013
|View full text |Cite
|
Sign up to set email alerts
|

3D Powder Printed Bioglass and β-Tricalcium Phosphate Bone Scaffolds

Abstract: The use of both bioglass (BG) and β tricalcium phosphate (β-TCP) for bone replacement applications has been studied extensively due to the materials’ high biocompatibility and ability to resorb when implanted in the body. 3D printing has been explored as a fast and versatile technique for the fabrication of porous bone scaffolds. This project investigates the effects of using different combinations of a composite BG and β-TCP powder for 3D printing of porous bone scaffolds. Porous 3D powder printed bone scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Calcium phosphates are a commonly used material, based on their osteointegrative and osteoconductive characteristics. In the body, calcium phosphates form a hydroxyapatite layer, an essential ingredient for bone formation that enhances tissue integration [131]. A study that compared the suitability of β-TCP and bioglass combinations of scaffold materials found that in load bearing applications, the mechanical techniques were limited by 3D printing, despite their biocompatibility properties [131].…”
Section: Cv-tebg and Nanotechnology-related Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium phosphates are a commonly used material, based on their osteointegrative and osteoconductive characteristics. In the body, calcium phosphates form a hydroxyapatite layer, an essential ingredient for bone formation that enhances tissue integration [131]. A study that compared the suitability of β-TCP and bioglass combinations of scaffold materials found that in load bearing applications, the mechanical techniques were limited by 3D printing, despite their biocompatibility properties [131].…”
Section: Cv-tebg and Nanotechnology-related Scaffoldsmentioning
confidence: 99%
“…In the body, calcium phosphates form a hydroxyapatite layer, an essential ingredient for bone formation that enhances tissue integration [131]. A study that compared the suitability of β-TCP and bioglass combinations of scaffold materials found that in load bearing applications, the mechanical techniques were limited by 3D printing, despite their biocompatibility properties [131]. The review by Popov et al gives the example of titanium 3D printed implant, admitting that the use of metal is a novelty in implantations and therefore there are a lot of questions needing to be answered before undergoing clinical trials [128].…”
Section: Cv-tebg and Nanotechnology-related Scaffoldsmentioning
confidence: 99%
“…Doping the TCP scaffold with bioactive compounds can improve biocompatibility [ 103 ]. To facilitate bone formation and faster mineralization, TCP scaffolds were doped with SrO and MgO [ 104 ].…”
Section: Powder Bed Inkjet Printingmentioning
confidence: 99%
“…However, traditional fabrication methods do not allow fabrication of complicated porous structures with high resolution, therefore it has not been easy to predict the mechanical properties of designed scaffolds beforehand [9]. It was only the recent development of additive manufacturing (AM) technology, especially the powder bed fusion method, that allowed us to fabricate complicated porous scaffolds for hard tissue engineering [10,11].…”
Section: Introductionmentioning
confidence: 99%